2016
DOI: 10.1007/s10616-016-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxic and genotoxic evaluation of peptides used in nuclear medicine (DOTATATE and Ubiquicidin29-41) in CHO-K1 cells

Abstract: Micronucleus (MN) assay constitutes a valuable surrogate to the chromosome aberration technique for in vitro testing of the genotoxicity of substances. As test substances, two peptidic compounds (DOTATATE and Ubiquicidin) used in nuclear medicine, were tested for in vitro cytotoxicity and genotoxicity in CHO-K1 cells. None of the compounds showed detectable cytotoxicity (0.5-7.3 ng/mL for DOTATATE and 0.3-4.5 ng/mL for UBI), genotoxicity (0.72, 7.2 and 72.0 ng/ml for DOTATATE and 0.45, 4.5 and 45.0 ng/mL for U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
5
0
3
Order By: Relevance
“…A pooled meta-analysis of clinical studies with 99m Tc-UBI 29-41 showed 95% sensitivity, 93% specificity and 94% accuracy in various clinical settings including prosthetic infections, diabetic foot infections, fever of unknown origin, osteomyelitis, mediastinitis, and appendicitis [55,64,65]. Due to its ability to discriminate between infection and sterile inflammation, general safety, the lack of side effects [66][67][68][69], and the successful transformation to kit formulations [59,[70][71][72], radiolabelled UBI 29-41 has been proposed as a good candidate for applications in routine imaging [4,9,61]. Nevertheless, prospective multi-centre studies of both 99m Tc-and 68 Ga-UBI 29-41 should still be carried out to achieve robust evidence of the accuracy in clinical imaging of bacterial infections.…”
Section: Imaging Of Infections With Antimicrobial Peptidesmentioning
confidence: 99%
“…A pooled meta-analysis of clinical studies with 99m Tc-UBI 29-41 showed 95% sensitivity, 93% specificity and 94% accuracy in various clinical settings including prosthetic infections, diabetic foot infections, fever of unknown origin, osteomyelitis, mediastinitis, and appendicitis [55,64,65]. Due to its ability to discriminate between infection and sterile inflammation, general safety, the lack of side effects [66][67][68][69], and the successful transformation to kit formulations [59,[70][71][72], radiolabelled UBI 29-41 has been proposed as a good candidate for applications in routine imaging [4,9,61]. Nevertheless, prospective multi-centre studies of both 99m Tc-and 68 Ga-UBI 29-41 should still be carried out to achieve robust evidence of the accuracy in clinical imaging of bacterial infections.…”
Section: Imaging Of Infections With Antimicrobial Peptidesmentioning
confidence: 99%
“…Both PET analogues 68 Ga-NOTA-UBI 29-41 and 68 Ga-NOTA-UBI 31-38 showed comparable characteristics of uptake in infected femoral muscles in mice and rabbits. However UBI 29-41 was also accumulated in yeast-induced infections, which reduces the specificity of the use of this marker to visualize only the bacterial infections [40,41].…”
Section: Future Directionsmentioning
confidence: 99%
“…Embora outras modificações positivas possam ser possíveis nas metodologias de contagem por microscopia, (Ocampo et al, 2016) (Bryce et al, 2007). O experimento realizado com radiação foi feito para padronizar a técnica modernizada (citometria de fluxo).…”
Section: Discussionunclassified
“…Na maioria dos casos, eles não levam a células que carreguem mutações ou ainda que possam se reproduzir em formações neoplásicas. Isto porque tais danos geralmente são detectados e corrigidos por mecanismos de revisão do DNA e correção (Dexheimer, 2013 Tradicionalmente, este ensaio é realizado usando microscopia, (Ocampo et al, 2016), usando uma coloração convencional segundo Giemsa (Heddle et al, 2011)…”
Section: Mecanismos De Reparo Do Dnaunclassified